Evolution and comparative assessment of ambient air quality standards in China. Issue 2 (1st October 2016) - Zhao, Bingtao; Su, Yaxin; He, Shushen; Zhong, Mei; Cui, Guomin
Abstract: Ambient air pollution has become one of the key issues in China because it is highly associated with economic development, energy consumption, the atmospheric environment, and public health. Ambient air quality standards are guidelines of environmental management and fundamentals of air pollution emission control. To adapt to the changing environmental situation, China's ambient air quality standard GB 3095 was established in 1982, amended in 1996, again in 2000, and most recently in 2012. This article presents a historical analysis on the evolution of China's ambient air quality standards focusing on the critical pollutants and their concentration thresholds, as well as a comparative analysis that illustrates the differences to important developed countries and international organizations. The results show that the ambient air quality standard in China features a progressive update in pollutant items, more stringent concentration thresholds, and more scientific planning. Although there are differences in the economic, technological, and environmental development levels, China's latest ambient air quality standard GB 3095-2012 is found to be comparable with other important standards. However, the support of macro policies and technical measures are necessary to ensure the standard is implemented more effectively.